2022
DOI: 10.3389/fbioe.2022.833920
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Biology-Driven Microbial Production of Resveratrol: Advances and Perspectives

Abstract: Resveratrol, a bioactive natural product found in many plants, is a secondary metabolite and has attracted much attention in the medicine and health care products fields due to its remarkable biological activities including anti-cancer, anti-oxidation, anti-aging, anti-inflammation, neuroprotection and anti-glycation. However, traditional chemical synthesis and plant extraction methods are impractical for industrial resveratrol production because of low yield, toxic chemical solvents and environmental pollutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 100 publications
0
16
0
Order By: Relevance
“…Since oxidative stress is linked with the pathogenesis of PD 36 , any agent that can maintain the redox and oxidative stress-antioxidant balance might be a promising therapeutic drug for PD 37 . Resveratrol (3,5,4'-trihydroxystilbene) is a naturally existing polyphenolic compound found in nuts and fruits such grapes 38,39 . It has been reported to possess both anti-inflammatory and antioxidative properties 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Since oxidative stress is linked with the pathogenesis of PD 36 , any agent that can maintain the redox and oxidative stress-antioxidant balance might be a promising therapeutic drug for PD 37 . Resveratrol (3,5,4'-trihydroxystilbene) is a naturally existing polyphenolic compound found in nuts and fruits such grapes 38,39 . It has been reported to possess both anti-inflammatory and antioxidative properties 40 .…”
Section: Discussionmentioning
confidence: 99%
“…We rst demonstrated that ACFVA could accurately measure many different biologically important features of suspensions cells using several plant cell types, including live Arabidopsis protoplasts and Dunaliella cells because these cells are particularly challenging to identify by automated image analysis (Lobet et al, 2013;Sekulska-Nalewajko et al, 2016), and they enable rapid chemical substance detection such as pollutants in the environment or generation of large quantities of active ingredients such as Plant-derived therapeutic proteins using living cell after genetic modi cation (Feng et al, 2022;Liu and Stewart Jr, 2015). Using the basic cell-culture methods described previously (Hosseini Tafreshi and Shariati, 2009; Yoo et al, 2007), we prepared Arabidopsis protoplasts and Dunaliella cells for experiments shown in Figs.…”
Section: Validation Of Acfva For Different Plant Cellsmentioning
confidence: 99%
“…By contrast, automated analysis rapidly produces consistent, quantitative measures for every image (Stöter et al, 2013). This is very important for synthetic biology whose emphasis was engineering and conformity to obtain systems-level conclusions from the quantitative measures a large number of features even features undetectable by eye for every image (Feng et al, 2022;Schweizer, 1980).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, because malonyl-CoA is primarily employed as an important intermediary in fatty acid biosynthesis to maintain cell development, only a small amount of malonyl-CoA is available for resveratrol biosynthesis, which is a significant hurdle in resveratrol production. 40 Malonyl-CoA is converted from acetyl-CoA in a reaction catalysed by acetyl-CoA carboxylase (encoded by ACC1 ), which originated in the yeast cell from acetate. In its turn, acetate is derived from acetaldehyde that results from pyruvate or ethanol consumption, which can help to balance the supply of malonyl-CoA in the yeast cell (Fig.…”
Section: Introductionmentioning
confidence: 99%